Facet-joint injections for people with persistent non-specific low back pain (FIS): study protocol for a randomised controlled feasibility trial. Issue 1 (December 2015) - Sandhu, Harbinder; Ellard, David; Achana, Felix; Antrobus, James; Balasubramanian, Shyam; Brown, Sally; Cairns, Melinda; Griffiths, Frances; Haywood, Kirstie; Hutchinson, Charles; Lall, Ranjit; Petrou, Stavros; et al.
Abstract Background The role of injections of therapeutic substances into the back as treatment for low back pain is unclear. Facet joint injections are widely used despite the absence of evidence of sustained benefit. We hypothesise that facet joint injections might facilitate engagement with physiotherapist-led, best usual care (a combined physical and psychological programme) and is a clinically and cost-effective treatment for people with suspected low back pain of facet joint origin. Methods/Design We present here the protocol for a randomised controlled feasibility trial for a main trial to test the above hypotheses. Patients referred to secondary care with persistent non-specific low back pain will be screened and invited to take part in the study. Those who meet the eligibility criteria will be invited for a physiotherapy assessment to confirm trial eligibility and for baseline data collection. All participants (n  = 150) will be offered the best usual care package with physical and psychological components. Those randomised into the intervention arm (n  = 75) will, in addition, receive intra-articular facet joint injections with local anaesthetic and steroids. Primary outcome data will be collected using daily and then weekly text messaging service for a pain score on a 0–10 scale. Questionnaire follow-up will be at 3, 6, and 12 months. Evaluation of trial processes and health economic analyses, including a value of information analysis, will be undertaken. The process evaluation will be mixed methods and will include the views of all stakeholders. Discussion Whilst this trial is a feasibility study it is currently one of the largest trials in this area. The outcomes will provide some evidence on the use of facet joint injections for patients with clinically diagnosed facet joint pain. Trial registration EudraCT identifier 2014-000682-50, (registered on 12 February 14). ISRCTN registry number:ISRCTN93184143 DOI10.1186/ISRCTN93184143 (registered on 27 February 2014).